A Diagnostic Nomogram of Pathologic Grade for Preoperative Risk Stratification in Upper Tract Urothelial Carcinoma. (June 2020) - Ma, Runzhuo; Xia, Haizhui; Qiu, Min; Tao, Liyuan; Lu, Min; Huang, Rui; Lu, Jian; Ma, Lulin
Background: To develop a novel nomogram to improve the preoperative diagnosis of pathological grade of upper tract urothelial carcinoma (UTUC). Methods: Retrospective study was conducted with 245 patients with UTUC treated by radical nephroureterectomy from 2002 to 2016. Of the cohort, 57.6% received ureteroscopic (URS) biopsy and 35.9% received urine cytology examination. Preoperative clinical characteristics and examination results were collected. Final pathological grade was diagnosed by postoperative pathology. Univariable and multivariable binary logistic regressions were applied to establish a preoperative predictive model for tumor grade, and significant factors were included in the nomogram. The area under curve (AUC) was used to show the predictive efficacy, and the calibration plot was drawn for validation. Results: Of the 245 patients, 72.7% were diagnosed with pathological high-grade disease. Age (odds ratio [OR] = 1.03, P  = .039), sessile (OR = 3.86, P  = .021), positive urinary cytology (OR = 6.87, P  = .035), and biopsy high-grade result (OR = 10.85, P  < .001) were independent predictors for pathological high-grade disease. The predictive nomogram containing these factors achieved an AUC of 0.78, which was significantly better than URS biopsy alone (AUC = 0.62, P  = .003) in the whole cohort. In the URS biopsy subgroup, the nomogram achieved an AUC of 0.79, better than biopsy alone (AUC = 0.76), but was not statistically significant ( P  = .431). When the cutoff value of the nomogram was set at 0.64, the sensitivity of detecting a high-grade lesion versus low-grade lesion was 80.3%, better than that of URS biopsy alone (sensitivity = 65.7%). Conclusions: Advanced age, sessile, positive urinary cytology, and biopsy high-grade were independent predictors of pathological high-grade disease in patients with UTUC. A nomogram containing these factors can improve diagnostic accuracy, potentially reducing the risk of "undergrading" by URS biopsy.